Framing Brecht and the Greek Student Movement (1972-1973) - Asimakoulas, Dimitris (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis paper examines the subversive function of an anthology of Bertolt Brecht’s political essays that was published in Greece at the time the student movement was emerging. The collection was launched in 1971, four years after the military coup in Greece. Drawing on the notion of frame from social movements theory, the paper focuses on the trajectory of the Greek student movement and the main frames that brought it forward as the most successful form of resistance against the junta. Then the paper illustrates how the Brecht anthology in particular captures the general climate of cultural and political opposition that created the resonance deemed necessary for the success of the student movement.